MORALITAS HUKUM DALAM HUKUM PRAKSIS SEBAGAI SUATU KEUTAMAAN - Subiharta, Subiharta (Jurnal Hukum dan Peradilan, 2015)
Morality without law is powerless and law without morality is meaningless. Practical law as a virtue emphasizes on morality, providing justice, legal certainty, balance and expediency. Practical law isn’t the kind of law in the sense of merely black and white, but it is one that is able to make change in society, have and ethical dimension, contain legal values which live among people in the community.Keywords: Legal Morality, Virtue of Practical Law, Justice, Legal Certainty, Balance, Expediency